PENGARUH AUDIT TENURE, KOMITE AUDIT, FINANCIAL STABILLITY TERHADAP INTEGRITAS LAPORAN KEUANGAN - Hidayat, Nuzullia Nurul; Suciati Muanifah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the Effect of Audit Tenure, Audit Committee, and Financial Stability on Financial Statement Integrity. In this study, the independent variables used are Audit Tenure, Audit Committee, and Financial Stability, while the dependent variable used is Financial Statement Integrity. The type of data used in this study is secondary data. The population in this study is non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2019-2023 with a population of 129 companies. Samples were collected using a purposive sampling method with 20 companies as samples. The analytical method used is panel data regression analysis. The results of this study indicate that audit tenure, audit committee, and financial stability simultaneously influence the integrity of financial statements. Partially, only audit tenure has a negative effect on the integrity of financial statements, while the audit committee and financial stability have no effect on the integrity of financial statements.